Systemic Inflammatory Response After Open, Laparoscopic and Robotic Surgery in Endometrial Cancer Patients - Pilka, Radovan; Marek, Radim; Adam, Tomas; Kudela, Milan; Ondrová, Dana; Neubert, David; Hambálek, Jozef; Maděrka, Martin; Solichová, Dagmar; Krčmová, Lenka Kujovská; Melichar, Bohuslav (Anticancer research, 2016)
AIM: To study inflammatory response and nutritional biomarkers in operated endometrial cancer (EC) patients. MATERIALS AND METHODS: A total 109 consecutive EC patients undergoing open laparotomy (LT), laparoscopic (LS) or robot-assisted surgery (RS) were studied. Twenty four patients served as controls. Pre- and postoperative levels of inflammatory and nutritional biomarkers were analyzed prospectively. RESULTS: The estimated blood loss was significantly lower in RS compared to all other groups. C-reactive protein (CRP) and interleukin-6 (IL-6) correlated with each other and exhibited positive correlation with age, body-mass index (BMI), leukocyte count, platelet count, kynurenine, kynurenine/tryptophan ratio and urinary neopterin and a negative correlation with vitamin D and retinol. Hemoglobin, retinol, alpha-tocopherol, vitamin D and citrulline concentrations decreased and inflammatory biomarkers increased after surgery to a different extent in LT, LS, RS and control groups. CONCLUSION: The present data demonstrate a differential response to surgical trauma in patients with endometrial carcinoma.
Keywords: roboticky asistované výkony; Humans; laparoskopie; neopterin; lidé středního věku; C-reaktivní protein; robotic surgery; Female; Aged; Interleukin-6; dospělí; Endometrial Neoplasms; Inflammation; senioři; lidé; Biomarkers; Endometrial cancer; zánět; Adult; biologické markery; ženské pohlaví; Robotic Surgical Procedures; Middle Aged; interleukin-6; Neopterin; Aged, 80 and over; Laparoscopy; nutrition; senioři nad 80 let; nádory endometria; surgical trauma; inflammatory response; prospektivní studie; C-Reactive Protein; Prospective Studies